Analgesic Effects and Safety of Dexmedetomidine Added to Nalbuphine or Sufentanil Patient-Controlled Intravenous Analgesia for Children After Tonsillectomy Adenoidectomy - Jia, Yingping; Zhou, Rui; Li, Zhengchen; Wang, Yuanyuan; Chen, Sandong; Zhao, Liyuan; Shao, Yi; Qi, Jinlian (Frontiers in Pharmacology, 2022)
Tonsillectomy with and without adenoidectomy is a frequently performed surgical procedure in children, requiring post-operative analgesia. This study evaluated the efficacy and safety of nalbuphine or sufentanil combined with dexmedetomidine for patient-controlled intravenous analgesia (PCIA) after pediatric tonsillectomy adenoidectomy. A total of 400 patients undergoing tonsillectomy with and without adenoidectomy were included. Patients received a PCIA pump (0.5 mg/kg nalbuphine, 2 μg/kg dexmedetomidine and 0.9% sodium chloride to a total volume of 100 mL) for postoperative pain management were classified into Group ND (n = 200). Patients received a PCIA pump (2 μg/kg sufentanil, 2 μg/kg dexmedetomidine and 0.9% sodium chloride to a total volume of 100 ml) for postoperative pain management were classified into Group SD (n = 200). More stable hemodynamic changes were noted in Group ND than Group SD from 1 h to 48 h after operation. At 6, 12, 24, and 48 h after operation, the children in Group ND had higher Ramsay sedation scores than those in Group SD. The times to push the PCIA button in Group ND and Group SD were 2.44 ± 0.74 and 2.62 ± 1.00 (P = 0.041). The VASR scores of children in Group ND were significantly lower within 6, 12, and 24 h than those in Group SD (P < 0.05). The VASC scores of children in Group ND were significantly lower within four time points (2, 6, 12, and 24 h) than those in Group SD (P < 0.05). At 1st day after surgery, the children in Group ND had lower levels of serum ACTH, IL-6, and COR levels than those in Group SD (P < 0.001). The incidence rates of nausea and vomiting, and pruritus were significantly higher in Group SD than Group ND (5.00% vs. 11.00%, P = 0.028; 1.00% vs. 4.50%, P = 0.032). The total incidence rate of adverse reactions was significantly higher in Group SD than Group ND (15.00% vs. 31.00%, P = 0.0001). The study demonstrated that dexmedetomidine added to nalbuphine PCIA enhanced the analgesic effects, attenuated the postoperative pain, and reduced the stress response after pediatric tonsillectomy adenoidectomy.